The Aramaic epigraphical material of Syria-Palestine during the Persian period with reference to the history of the Jews - Klingbeil, Gerald A.,1964- (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.A.) -- University of Stellenbosch, 1992.